Accountability in University System in Nigeria: Challenges and Way Forward - Niyi Jacob Ogunode; Mbaocha Adolphus Obioma; Attiku Muazu Belloh (Journal of Artificial Intelligence and Digital Economy, 2024)
This paper looked at Accountability in the University system in Nigeria and its Challenges. Secondary data were adopted for the paper. The secondary data were collected from online and print publications. The paper concluded that lack of political will, weak accountability culture, weak labour unions, weak participation of stakeholder, poor implementation of accountability policies, poor monitoring of universities by anti-corruption agencies and other regulatory institutions, political influence and lack of autonomy amongst others are the factors responsible for poor accountability in the university system in Nigeria. To address these challenges, the paper suggested that Federal and State Governments should develop the political will to ensure visitation panels are constituted every five years and the white paper released should be implemented as at when due, to promote accountability in the universities. University administrators and managers should be trained and retrained on the importance of ensuring and promoting the culture of accountability in the universities. The various labour unions in the universities should be proactive in ensuring accountability in the universities. Also, autonomy should be granted to the universities to eliminate political influence activities in the universities.